2002
DOI: 10.1007/s00404-002-0378-4
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcome of septate uterus after hysteroscopic metroplasty

Abstract: We evaluated the reproductive outcome after hysteroscopic metroplasty in the patients with septate uterus. The reproductive performance of 361 patients with septate uterus during the follow-up period of 18 months after the surgery was analyzed retrospectively for a period of 10 years. A total of 180 (49.8%) pregnancies were achieved after metroplasty during the follow-up period of 18 months. Of the 180 pregnancies 117 (57.2%) reached to term and 34 (18.8%) ended in preterm delivery and the remaining 29 (16%) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 12 publications
1
26
0
4
Order By: Relevance
“…For example, Fedele et al [9] reported a 3‐year cumulative pregnancy rate of 39% in the infertile patient group and 62% in the abortion group; however, there were additional factors that might have caused infertility in 13 of the 31 infertile patients in that study. Saygili et al [19] found an 18‐month cumulative pregnancy rate of 23.3% in the infertile group and 83.1% in the habitual abortion group. In addition, Litta et al [20] reported a term pregnancy rate of 83% in patients with 1 or more abortion, and 53.3% in the infertile group [20].…”
Section: Discussionmentioning
confidence: 98%
“…For example, Fedele et al [9] reported a 3‐year cumulative pregnancy rate of 39% in the infertile patient group and 62% in the abortion group; however, there were additional factors that might have caused infertility in 13 of the 31 infertile patients in that study. Saygili et al [19] found an 18‐month cumulative pregnancy rate of 23.3% in the infertile group and 83.1% in the habitual abortion group. In addition, Litta et al [20] reported a term pregnancy rate of 83% in patients with 1 or more abortion, and 53.3% in the infertile group [20].…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that hysteroscopic resection of the septum in a septate uterus improves pregnancy outcome in subsequent pregnancies in women with recurrent miscarriages (Porcu et al, 2000;Saygili-Yilmaz et al, 2003;Valli et al, 2004). Hysteroscopic adhesiolysis also improves pregnancy outcome in women with recurrent miscarriages (Goldenberg et al, 1995;Katz et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with M€ ullerian duct anomalies are known to have a higher incidence of infertility, repeating first trimester spontaneous abortion, intrauterine fetal growth retardation, fetal malposition, preterm labor, and retained placenta (1,2). The mean prevalence of these anomalies in the infertile women is 3.5%, and in women with recurrent abortion it is 13% (3).…”
mentioning
confidence: 98%